Retrograde Balloon Dilation outside the Main Branch Stent to Restore the Occlusion of Side Branch in Chronic Total Occlusion Bifurcation Lesions - Gao Hao-kao; Li Cheng-xiang (Case Reports in Cardiology)
Percutaneous coronary intervention (PCI) of a chronic total occlusion (CTO) can be challenging when a bifurcation is present at the distal cap. We described a case of retrograde balloon outside the main branch stent to restore the occlusion of side branch in CTO bifurcation lesion through the jailed wire.